Hepatozoon parasites (Apicomplexa: Hepatozoidae) in fish Hoplias aimara (Characiformes, Erythrinidae) from the Eastern Amazon, Brazil - Cardoso, Wagner Amanajás; Perles, Lívia [UNESP]; Picelli, Amanda Maria; Correa, Jamille Karina Coelho; André, Marcos Rogério [UNESP]; Viana, Lúcio André (Springer Nature, 2022)
This study reports the occurrence of parasites belonging to the Hepatozoon genus in fish Hoplias aimara from the Eastern Amazon. Fish (n = 54) were sampled from the Falsino River, located in the Amapá National Forest (FLONA), in the state of Amapá, northern Brazil. Fresh liver preparations were examined in the field between a slide and a coverslip under a light microscope. Cysts containing Hepatozoon cystozoites were observed in the liver of 5 (9%) out of 54 H. aimara individuals. The cysts were ovoid (mean dimensions 10.28 × 9.8 μm), presenting up to four elongated cystozoites (mean dimensions 11.04 × 1.68 μm), containing 1 to 4 residual bodies of different sizes. A single liver sample containing cysts was submitted to DNA extraction and PCR analyses based on a fragment of the 18S rRNA gene. The sequencing revealed a 465 bp fragment exhibiting 99% query coverage, 0.0 E-value, and 98.7% identity with Hepatozoon caimani (MF322538 and MF322539), detected in caimans (Caiman yacare) from Brazil. This is the first report of the occurrence of cysts containing Hepatozoon cystozoites in free-living fishes.
Keywords: 18S rRNA gene; Floresta Nacional do Amapá; Paratenic hosts; Trophic transmission